2013
DOI: 10.1177/1948550613492826
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Political Orientation, and Consequentialist Moral Thinking

Abstract: Three studies demonstrated that the moral judgments of religious individuals and political conservatives are highly insensitive to consequentialist (i.e., outcome-based) considerations. In Study 1, both religiosity and political conservatism predicted a resistance toward consequentialist thinking concerning a range of transgressive acts, independent of other relevant dispositional factors (e.g., disgust sensitivity). Study 2 ruled out differences in welfare sensitivity as an explanation for these findings. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 38 publications
11
118
0
Order By: Relevance
“…Specifically, Divine Command beliefs were central in explaining why religious believers are relatively committed to moral rules in the face of utilitarian alternatives. Consistent with Piazza and Sousa's (2013) rationale, it would seem that religious individuals are often ruleoriented because they view moral rules as grounded in God's supreme moral authority.…”
Section: Moral Cognitionmentioning
confidence: 98%
See 3 more Smart Citations
“…Specifically, Divine Command beliefs were central in explaining why religious believers are relatively committed to moral rules in the face of utilitarian alternatives. Consistent with Piazza and Sousa's (2013) rationale, it would seem that religious individuals are often ruleoriented because they view moral rules as grounded in God's supreme moral authority.…”
Section: Moral Cognitionmentioning
confidence: 98%
“…However, among contemporary Christian samples, a belief in divine moral authority appears to BELIEF IN DIVINE MORAL AUTHORITY 7 undergird a deontological approach to morality via commitments to follow divine ordinances, which generally take the form of moral rules (Piazza, 2012;Piazza & Landy, 2013;Piazza & Sousa, 2013). Research by Piazza and colleagues has found that people who endorse DCT tend to think that moral rules should be followed even when breaking them would help promote a greater good.…”
Section: Divine Command Theory (Dct) and Its Role In Moralitymentioning
confidence: 99%
See 2 more Smart Citations
“…I thought that endorsement of open-mindedness would be seen as socially desirable. Some insight about one source of the low scores came from the work of Jared Piazza ([30] [31] [32]), who found that consequentialist and utilitarian judgments were negatively correlated not only with political conservatism and religiosity but, especially, with a belief in "divine command theory," the claim that people are incapable of understanding or questioning God's moral pronouncements and should not try to do so. Baron et al [29] found that a measure of belief in this theory was strongly negatively correlated with the self-report AOT scale and with utilitarian moral judgment.…”
mentioning
confidence: 99%